The role of religion in peacebuilding: Indonesia’s experience - Humaidi; Sahri, Iksan Kamil (Penerbit Universiti Kebangsaan Malaysia, 2020)
Indonesia is a very plural and multicultural nation. The diversity is not only in religious aspect but also in ethnicity, culture and language. There is surely a clash or friction in it due to the diversity, but peoples remain lives in peace, harmony and mutual respect in those differences. Religion which is held majority of Indonesian plays important role in this “unity in diversity” life. Religion becomes the main path in achieving unity and harmony and has become the reason for an existence (raison d'etre), a connector and a binder for all elements of society to always live in harmony and peace. Without religion, it is impossible to build unity and peace. It became the main capital, basic foundation, and determinant for solidarity, peace and harmony in this archipelago country (Nusantara). This article will explain and analyze the role of religion in building unity and peace in Indonesia by observing the past and present realities. Through this article, the researcher also tries to refute those who stated that religion is a source of conflict, chaos and roots of radicalism. This research is qualitative using a historical-hermeneutical approach and philosophical analysis.